Chinese herbal medicine improves antioxidant capacity of chicken liver at high stocking density involved gut-liver microbiota axis based on multi-omics technologies - Hongbin Pan; Junlong Bi; Hong Hu; Ying Huang; Anjian Li; Hao Zhang; Yi Wan; Kai Zhan; Kunping Wang; Zelong Zhao; Xi Bai (Poultry Science)
Traditional Chinese Medicine (TCM), such as artemisinin, berberine and proanthocyanidin, has been considered an effective additive for broiler production. High density farming (HDF), which is the primary modern mode of chicken production, is associated with animal health problems. This work aimed to evaluate the effects of dietary TCMs (dihydroartemisinin, hydrochloride, and oligomeric proanthocyanidins) on improving the antioxidant capacity of chickens under HDF and their underlying mechanisms. A total of 360 Wuding chickens (134-day-old) were divided into five experimental groups: one normal stocking density (8 birds/m2, control group) and four high stocking density (16 birds/m2), with six replicates for each group. For four HDF groups, one group was fed the basal diet, and the other three groups were fed the basal diet supplemented with 80 mg/kg dihydroartemisinin, 600 mg/kg berberine hydrochloride, and 250 mg/kg grape oligomeric proanthocyanidins, respectively. HDF increased malondialadehyde level, but decreased superoxide dismutase, glutathione and glutathione peroxidase levels in the liver of broiler; however, dietary TCMs apparently alleviated this attenuation. Dietary TCMs significantly decreased the expression of genes involved in cholesterol synthesis in the liver and the levels of tripepides in the intestine of the HDF chickens. Meanwhile, dietary TCMs significantly altered the composition of the liver microbiome in the HDF chickens, expressing by reduced Pseudomonas but enriched Bradyrhizobium. The gut microbiota of the HDF chickens was also altered following dietary TCM administration, with a decreased abundance of Microbacter margulisiae and an increased abundance of acetate synthesis genes. Association analysis of the multi-omics results revealed negative correlations between liver cholesterol synthesis and antioxidant factors that could be regulated by gut microbiota-produced short-chain fatty acids. Furthermore, alleviating of oxidative stress by dietary TCMs also showed significant correlations with the liver microbiome, which could be mediated by tripeptides produced by the gut microbiota. These results indicated that dietary TCM is beneficial in improving antioxidant defenses in HDF chickens and interpreted the mechanisms of action of TCM from the perspective of modern science.